References in Le Corbusier’s reorganization of rural habitat - Arredondo-Garrido, David (Journal of Architecture and Urbanism, 2016)
Projects for the Reorganization of the Rural Habitat designed by Le Corbusier during the ‘30s posed a territorial model from a radically new vision. The Ferme Radieuse, the Village Radieux and its implementation as the Unité d’Explotation Agricole within his theory of Les Trois Établissements Humains, form a complex theory of agricultural land use with an innovative character. However, in these studies some historical and vernacular references can also be found. They significantly influenced the overall approach and the results.Thanks to his relationship with the rural activist Norbert Bézard and a direct contact with farmers in the region of Sarthe, in central France, Le Corbusier began to understand their problems, needs and ways of working. He approached, at the same time, to some theoretical reflections from French rural historians and geographers, such as Roupnel and Ramuz. Influence from writers like Ritter or politicians like Giradoux, together with its own interests, marked his later designs. Besides the accepted functionalist scheme, we can also find in this Reorganization of the Rural Habitat some interesting historical connections as well as a nostalgic attempt to recover past and vernacular models.